Resurrecting the shark : a scientific obsession and the mavericks who solved the mystery of a 270-million-year-old fossil /: a scientific obsession and the mavericks who solved the mystery of a 270-million-year-old fossil. ([2017]) - Ewing, Susan, 1954-
No abstract available